2014
DOI: 10.1002/mnfr.201400269
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis reveals a dynamic and differential transcriptional response to sulforaphane in normal and prostate cancer cells and suggests a role for Sp1 in chemoprevention

Abstract: Epidemiological studies provide evidence that consumption of cruciferous vegetables, like broccoli, can reduce the risk of cancer development. Sulforaphane (SFN) is a phytochemical derived from cruciferous vegetables that induces anti-proliferative and pro-apoptotic responses in prostate cancer cells, but not in normal prostate cells. The mechanisms responsible for this cancer-specific cytotoxicity remain unclear. To examine this issue we utilized RNA sequencing and determined the transcriptomes of normal pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 43 publications
2
30
1
Order By: Relevance
“…The exact mechanism is not clear but early research has revealed other transcription factors are also involved in VEGF expression, such as Sp1/ Sp3, AP2, Egr-1 and STAT-2 (44). For example, SFN was found to be able to inhibit STAT and SP1 pathways (45,46). Our finding may suggest that SFN has a potential role in attenuating anticancer resistance.…”
Section: Discussionmentioning
confidence: 58%
“…The exact mechanism is not clear but early research has revealed other transcription factors are also involved in VEGF expression, such as Sp1/ Sp3, AP2, Egr-1 and STAT-2 (44). For example, SFN was found to be able to inhibit STAT and SP1 pathways (45,46). Our finding may suggest that SFN has a potential role in attenuating anticancer resistance.…”
Section: Discussionmentioning
confidence: 58%
“…Normal prostate epithelium cells (PREC) were obtained from Lonza (Basel, Switzerland) and cultured as recommended (Lonza) [18, 21]. Androgen-dependent (LNCaP) and androgen-independent (PC-3) prostate cancer cells were obtained from American Type Tissue Collection (Manassas, VA) and cultured as previously described [18].…”
Section: Methodsmentioning
confidence: 99%
“…Cells were treated in triplicate, and total RNA was isolated and subsequently sequenced on an Illumina HiSeq 2000 machine at the Center for Genome Research and Biocomputing core facility at Oregon State University as previously described [21]. Sequencing data were processed in two separate pipelines.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations